Enhanced Dual-Vector Model Predictive Current Integrated Control for Electric-Drive- Reconstructed Onboard Chargers - Feng Yu; Qihao Yin; Laiwu Luo; Yuhao Zhang (IEEE Access)
Electric-drive-reconstructed on-board chargers (EDROCs) have emerged as a viable solution to alleviate mileage anxiety in electric vehicles (EVs) over the past decade. Nevertheless, the inclusion of additional components and separate control strategies in the previous EDROCs undeniably results in an escalation of system cost and control complexity. To address such an issue, an enhanced dual-vector model predictive current integrated control (MPCIC) for EDROCs is proposed, which is designed for the solar-powered electric vehicle (SPEV) that is equipped with a symmetrical six-phase machine. Firstly, the proposed topology implements the integration of charging and driving operations by re-leveraging the inherent traction system, significantly minimizing the incremental components. Secondly, the integrated control strategy for all operation modes is devised by incorporating the enhanced dual-vector model predictive control (MPC), mitigating the complexities and enhancing reliability. In this enhanced MPC, 12 virtual vectors, which consist of two active vectors, along with the optimized cost function are introduced, effectively suppressing harmonic currents. To this end, the effectiveness of the proposed EDROC is verified through a 2-kW experimental prototype under different operation modes.